2020
DOI: 10.1109/access.2020.2979687
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Mobile Relays Positions and Resource Allocation for Multi-Relay Multi-Destination Wireless Networks

Abstract: Deploying relays is a major means to improve the performance of wireless networks. In this paper, multiple mobile relays carried by smart drones are sent by a source to assist the communication to multiple destinations for the Public Safety Wireless Broadband Network, where the sole source is not sufficient to satisfy the quality of service (QoS) requirement of all destinations. With Rician fading between source and relays, and relays and destinations, we study two related questions: The first is where to depl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Figure 20 shows the visited-wise comparison among EAMDSP, CDSSSD and MDMSMD as per Table 22. Finally, based on Figures 13,14,19,and 20,and Tables 13,14,21,and 22 it is reported that the proposed EAMDSP demonstrates the outstanding performance on cost and number of visited nodes compared to CDSSSD and MDMSMD.…”
Section: Sl No Algorithm Name Total Visited Nodesmentioning
confidence: 87%
See 1 more Smart Citation
“…Figure 20 shows the visited-wise comparison among EAMDSP, CDSSSD and MDMSMD as per Table 22. Finally, based on Figures 13,14,19,and 20,and Tables 13,14,21,and 22 it is reported that the proposed EAMDSP demonstrates the outstanding performance on cost and number of visited nodes compared to CDSSSD and MDMSMD.…”
Section: Sl No Algorithm Name Total Visited Nodesmentioning
confidence: 87%
“…The MDMSMD calculates the shortest path from each source to each destination node, the previous destination node is the next source node, and calculates the shortest path from the next source to the next destination node until the last destination node. This algorithm can only calculate the shortest path between one pair at a time [20], it cannot calculate the shortest path between a source node and a set of destination nodes at the same time. The objective of this research is to develop an efficient algorithm for searching the smallest path between a given source and the multi-destination nodes.…”
Section: S = S U{vm} L = L\{vm}mentioning
confidence: 99%